Estudo sobre dor lombar crônica e depressão de idosos - Donatti, Ariel (Universidade Federal de São Carlos, 2019)
Population ageing causes an increase in the prevalence of chronic diseases and functionality impairment. The depressive symptoms and chronic lumbar pain have been affecting a growing number of senior persons and have become important subjects of investigation. In that sense, this study was designed to determine the relationship between the intensity of the lumbar pain, the impairment generated by that pain and the presence of depressive symptoms in senior persons who are independent in their basic daily activities. The character of the study was descriptive, qualitative and cross-sectional. We analyzed a sample of independent elderly persons suffering from chronic lumbar pain (n=46) registered at the Family Health Units (Unidades Saúde da Família) in the municipality of São Carlos, São Paulo state. The following items were use to collect data: Elderly Characterization Record, Multidimensional Pain Assessment Scale - EMADOR (MPAS), Roland-Morris Disability Questionnaire and the Geriatric Depression Scale - GDS. The data collected were input into a databank in the software Statistical Package for Social Sciences (SPSS) for Windows to perform descriptive analyses and a Spearman correlational analysis. The National Health Council ethic guidelines regarding research with human beings were fully respected. Most senior persons describe their lumbar pain as painful, persistently and uncomfortably. The results indicate that more intense pain negatively affects appetite, interpersonal relationships and mobility. The correlational analyses have demonstrated a significant relationship between the intensity of the lumbar pain and the number of depressive symptoms with a weak and directly proportional magnitude (rho=0.302, p=0.041). Besides, we observed a significant relationship between the number of disabilities/ limitations caused by the lumbar pain and the number of depressive symptoms with a moderate and directly proportional magnitude (rho=0.403, p=0.005).
Study on chronic lumbar pain and depression in senior persons
Keywords: Dor crônica; Dor lombar; Depressão; Transtorno depressivo; Idoso; Saúde do idoso; Incapacidade; Gerontologia; Chronic pain; Lumbar pain; Depression; Depressive disorder; Elderly, Health of The elderly; Disability; Gerontology; CIENCIAS DA SAUDE